Public Education Expenditure and Other Determinants of Private Investment in the Caribbean - Levy, Joaquim; Clements, Benedict (Washington, D.C. : International Monetary Fund, 1994)
This paper presents an analysis of the determinants of private investment in the Caribbean region, using data for the 1977-91 time period. Drawing on the endogenous growth literature, a model is developed to capture the impact of public education expenditure on private sector capital formation. The implications of this model are tested in the context of an econometric model assessing the impact of education and other variables on the share of private investment in GDP. The empirical results reveal that public education outlays, as well as economic growth, have a significant effect on private capital formation. Public investment has a negative effect on private investment, while real interest rates and external debt burdens are found to have no statistically significant impact on private investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet